Measuring Agency-Level Results: Lessons Learned from Catholic Relief Services’ Beneficiary and Service Delivery Indicators Initiative - Harry Carr; Kelly M. Scott (Journal of MultiDisciplinary Evaluation, 2017)
Background: Many NGOs have less success documenting their results at the agency level than at the program or project level. Little has been published on the challenges NGOs face in developing and measuring agency-level results. To address this issue, InterAction, an alliance of NGOs, commissioned a comparative study that drew on the existing grey literature, and a sample of 17 InterAction member organizations through case studies and interviews.